The 346 Clause of TFEU Regulation in Different EU Member States - Kuzminskas, Vilius (Teisė, 2019)
The article discloses the fixed exclusion regulation of Clause 346 in the Treaty of Function of the European Union in different EU member states. A further assessment of different relevant judicial approaches to regulation are disclosed and evaluated in accordance with the European Court of Justice case law and procurement in the defense area doctrine.
Keywords: public procurement; defence and security; TFEU article 346; directive 2009/81